Prevalence of antral pseudocyst and apical mucositis in the maxillary sinus as common entities found in panoramic x-rays among patients at a radiological center in Huacho, Lima, Peru, 2019 - Hinostroza Paz, Geraldine (2023)
Maxillary sinuses are directly related to the dentoalveolar process, so knowledge of the pathologies that may affect and compromise either of the two structures can facilitate a correct diagnosis and treatment. Objective: To determine antral pseudocyst and apical mucositis prevalence as frequent entities found in panoramic x-rays among patients at a radiological center in Huacho, Lima, Peru, 2019. Material and Methods:Cross-sectional, observational, descriptive and retrospective study. From a total of 1,646 virtual panoramic x-rays collected at a radiological center in Huacho, 1,224 x-rays were used as sample population after taking into account the inclusion and exclusion criteria. The variables were antral pseudocyst, thickening of the mucosa, apical periodontitis, apical mucositis, age, gender, and month in which x-ray was taken. Descriptive and bivariate analysis was performed. Results: Antral pseudocyst of respiratory origin prevalence was 5.71%, mucositis prevalence was 13.07%, and prevalence of both correlated entities was 0.90%. A significant association was found between the presence of antral pseudocyst of respiratory origin and male gender (p=0,007). Conclusion: The occurrence of apical lesions leading to both thickening of the antral mucosa and the presence of odontogenic antral pseudocysts, while not rare, was found to be of low prevalence.